Adult learners’ barriers of learning: the world of married women - Ariwijaya, Toni; Ningsih, Lale Fatma Yulia (COUNS-EDU: The International Journal of Counseling and Education, 2020)
The composition of university population has prompted researchers to examine the barriers of learning non-traditional students, typically 24 years old or older, encounter in their pursuit of a college education. The purpose of this study is to examine the live realities of six selected female adult learners in Universitas Islam Al-Azhar Mataram, Indonesia, as the institution provides programs for adult learners. Specifically, the study focuses on three types of barriers; situational, institutional and dispositional. In doing so, semi-structured interviews and focus group discussions had been conducted for two academic calendars. Interviews were digitally recorded, transcribed verbatim and individual transcriptions were checked for clarity. The findings of this study reveal that cultural and personal aspects were strongly correlated with academic and non-academic struggles. Meanwhile, it is suggested that, for female adult learners to successfully overcoming the barriers, there is a need from college institutions to create more avenues of support.